Ð PREVALENCE AND RISK FACTORS FOR INSULIN RESISTANCE AND DYSGLYCEMIA AFTER KIDNEY TRANSPLANTATION IN PATIENTS ON CYCLOSPORINE-A BASED IMMUNOSUPPRESSION - Petkovska, Lidija; Simonovska, Natasha; Babulovska, Aleksandra; Huseini, Afrodita Berat; Kavrakova, Julijana Brezovska; Petronijevik, Zvezdana; Ivanovska, Beti Zafirova (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Posttransplantation disturbances in glucose metabolism and increased insulin resistance  are major factors affecting overall cardiovascular morbidity, reduced graft function, and survival after renal transplantation. We analyzed the prevalence of increased insulin resistance simultaneously with the prevalence of pre-diabetes in kidney transplant patients receiving a Cyclosporine-A based immunosuppression, and analyzed the risk factors for its occurrence, as well as the consequences on graft function. Fifty-nine  recipients of a living donor kidney, without previously diagnosed diabetes, were included in this cross-sectional and prospective study. All patients were on the same triple calcineurin inhibitor based immunosuppressive therapy at maintenance doses. In all of them, OGTT was performed at least 6 months after transplantation in order to determine the prevalence of glucose disorders, as well as to determine the indices for insulin resistance and insulin secretion. We also analyzed potential risk factors for their occurrence. According to the OGTT results, patients were divided into two groups: a group with dysglycemia and a group of normoglycemic patients. Graft function was also monitored after a certain follow-up period in both groups. The overall prevalence of glucose disturbances and insulin resistance was 33.9% (20/59) and 86.44% (51/59), respectively. In the group with dysglycemia, the prevalence of insulin resistance was 95% (19/20), while the beta -function index was decreased in 40% (8/20). The mean value of the insulin resistance index in the dysglycemic group was significantly higher (3.139 Â± 1.11) compared to the normoglycemic group (2.264Â±1.00),p Ë‚0.01. The most significant risk factors for increased insulin resistance in the group with dysglycemia were: shorter transplant period, higher doses of Cyclosporine-A, post-load insulin and the the insulin secretion index. In this group of patients, a significant decrease in e-GFR was observed after an average of 18 months of follow-up. The prevalence of IR after renal transplantation is high in all patients, and especially in patients with disorders of glucose metabolism. The routine application of OGTT as a diagnostic tool for occult diabetes and pre-diabetes and the determination of insulin resistance can contribute to reducing their prevalence, since most of the risk factors for their occurrence are potentially modifiable. Keywords: kidney transplantation, pre-diabetes, insulin resistance, immunosuppression